Investigations on energy assessment, conservation potential, and recovery opportunities for stenter machines based on the field trial. Issue 1 (31st March 2022) - Patel, Nikunjkumar; Parikh, Munjal; Basu, Surajit; Bade, Mukund
ABSTRACT: In this paper, energy assessment, conservation potential, and recovery opportunities are explored for a stenter machine as it is energy intensive and widely used in textile finishing plants. This work is based on factual data collected by rigorous and exhaustive field trials. Further, modified energy model equations are proposed to perform assessment and parametric analysis for the determination of the required energy, specific energy consumption, energy efficiency index, and energy conservation and recovery potential. It is important to note that the actual energy consumption is reduced to 730 kW (saving 10%) at optimal conditions. For efficient operation of the stenter machine, fabric speed, operating temperature, and recirculation ratio need to be kept as maximum as possible without altering fabric quality. Further, the energy flow diagram shows that exhaust out air contains considerable energy (884 kW), which can be recovered as (i) to preheat inlet air, reducing energy requirement by 7% and (ii) to heat water, recovering 170 kW (21% saving potential). Sensitivity index shows that operating temperature has a higher influence on the stenter machine performance; temperature below 130°C adversely affects it. Overall, 15–20% energy can be saved in the stenter by appropriately operating it at optimal condition.